Catering Contract of Restaurants in the English Law. A Comparative Analytical Study with Iraqi Civil Law - Ali, Yunus (Journal of Legal Sciences, 2022)
The Catering contract is considered as a type of hospitality contracts in the English common law of customary origins. Which is unwritten and based upon judicial precedents of the English courts. It is a complex contract of mixed nature، Is Regarded as a contract for the sale of meals of food and drink،, and is considered as a contract for supply of services concerning the preparation of food and drink، for providing them to the customer، as well as being a bailment contract. It is worth-bearing in mind that this contract is subject to the rules of three important English legislations: The Sale of Goods Act 1979، The Supply of Goods and Services 1982، The Consumer Protection Act 1987، and The Consumer Rights Act 2015. It is also worth-mentioning that a lot of Statutorily Implied Terms can be extracted from this contract. Whereas the Iraqi civil code No.40 of 1951 did not regulate expressly this contract within the nominate contracts، but the rules of both the contract of sale and enterprise can be applied to this contract، because it contains sale of food and drink، as well as other services closely related to it، which the restaurateur provides to the customer.